Prevalence of undetected chronic kidney disease in high-risk middle-aged patients in primary care: a cross-sectional study - Siebenhofer, Andrea; Loder, Christine; Avian, Alexander; Platzer, Elisabeth; Zipp, Carolin; Mauric, Astrid; Spary-Kainz, Ulrike; Berghold, Andrea; Rosenkranz, Alexander R. (Frontiers in Medicine, 2024)
The global health burden of chronic kidney disease (CKD) results from both the disease itself and the numerous health problems associated with it. The aim of this study was to estimate the prevalence of previously undetected CKD in middle-aged patients with risk factors for CKD. Identified patients were included in the Styrian nephrology awareness program "kidney.care 2.0" and data on their demographics, risk factors and kidney function were described. Methods: Cross-sectional analysis of baseline data derived from the "kidney.care 2.0" study of 40-65 year old patients with at least one risk factor for CKD (hypertension, diabetes, cardiovascular disease, obesity or family history of end-stage kidney disease). Participants were considered to have previously undetected CKD if their estimated glomular filtration rate (eGFR) was less than 60 ml/min/1.73 m 2 and/or albumin creatinine ratio (ACR) ≥ 30 mg/g. We calculated the prevalence of previously undetected CKD and performed multivariate analyses. Results: A total of 749 participants were included in this analysis. The prevalence of previously undetected CKD in an at-risk population was estimated at 20.1% (95%CI: 17.1 -23.6). Multivariable analysis showed age (OR 1.06, 95%CI: 1.02 -1.09), diabetes mellitus (OR 1.65, 95%CI: 1.12 -2.30) and obesity (OR: 1.55, 95%CI: 1.04 -2.30) to be independent predictors of CKD. The majority of patients with previously undetected CKD had category A2-A3 albuminuria (121 out of 150). Most patients with previously undetected eGFR < 60 ml/min/1.73 m 2 were in stage G3 (36 out of 39 patients). Conclusion: Pragmatic, targeted, risk-based screening for CKD in primary care successfully identified a significant number of middle-aged patients with previously undetected CKD and addressed the problem of these patients being overlooked for future optimized care. The intervention may slow progression to kidney failure and prevent related cardiovascular events.